Multiproduct Firms, Product Differentiation, and Market Structure - Luca Lambertini; Silvia Baranzoni; Patrizio Bianchi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
This paper provides a survey on the literature on multiple firms under either endogenous or exogenous product differentiation. The main aim is to identify the reasons why firms supply product lines rather than single goods. Factors pertaining to the demand side, such as brand loyalty and switching costs, are treated here. Moreover, the incentive towards product proliferation is investigated in connection with the issue of the persistence of monopoly. The consequences of product proliferation on social welfare are also discussed.
Keywords: 330